Australian marine sponge alkaloids as a new class of glycine-gated chloride channel receptor modulator. - Balansa, W; Islam, R; Gilbert, Daniel; Fontaine, F; Xiao, X; Zhang, H; Piggott, AM; Lynch, JW; Capon, RJ (Bioorganic & medicinal chemistry, 2013)
Chemical analysis of a specimen of the sponge Ianthella cf. flabelliformis returned two new sesquiterpene glycinyl lactams, ianthellalactams A (1) and B (2), the known sponge sesquiterpene dictyodendrillin (3) and its ethanolysis artifact ethyl dictyodendrillin (4), and five known sponge indole alkaloids, aplysinopsin (5), 8E-3'-deimino-3'-oxoaplysinopsin (6), 8Z-3'-deimino-3'-oxoaplysinopsin (7), dihydroaplysinopsin (8) and tubastrindole B (9). The equilibrated mixture 6/7 exhibited glycine-gated chloride channel receptor (GlyR) antagonist activity with a bias towards α3 over α1 GlyR, while tubastrindole B (9) exhibited a bias towards α1 over α3 GlyR. At low- to sub-micromolar concentrations, 9 was also a selective potentiator of α1 GlyR, with no effect on α3 GlyR-a pharmacology that could prove useful in the treatment of movement disorders such as spasticity and hyperekplexia. Our investigations into the GlyR modulatory properties of 1-9 were further supported by the synthesis of a number of structurally related indole alkaloids.